The Relationship between the Implementation of Health Protocols and Client Satisfaction at the Banjarmasin Health Center - Rohni Taufika Sari; Noor Amaliah; Zaqyyah Huzaifah (MBUnivPress, 2022)
Puskesmas is a type of first-level health service that has an important role in the national health system. The contribution of Puskesmas in controlling the spread of Covid-19 is very important, to be able to manage their resources effectively and efficiently so that they are expected to be able to break the chain of transmission from one individual to another, from one family to another, even on a wider community scale. Along with the 'New Normal' culture, the implementation of health protocols is a must to be implemented by the entire community, either individually, in groups or in existing organizational systems, including Puskesmas. In this case, The Indonesian Ministry of Health through the Directorate of Primary Health Services, the Director General of Health Services, has issued a regulation regarding the Technical Services of Public Health Centers during the Covid-19 Pandemic in 2020. The application of health protocols at health centers will lead to several changes in the pattern of services by health workers at health centers. The provision of health services by implementing health protocols in the New Normal era must maintain service quality. One indicator of service quality is the level of client satisfaction. Based on this, it is necessary to conduct research to determine whether there is a relationship between the application of health protocols and client satisfaction at the Banjarmasin Health Center. This study uses a quantitative method with a cross sectional approach, sampling technique with accidental sampling, the number of respondents is 50 people. Analysis of the data using chi square results obtained p value 0.109, so that p <0.05 (alpha); Based on statistical tests, it can be concluded that there is a significant relationship between the implementation of health protocols and client satisfaction at the Banjarmasin Health Center. In the current New Normal era, supporting facilities are increasingly complete in implementing health protocols at health centers such as the availability of hand washing tools and materials, , masks and service patterns based on health protocol policies, the client will feel safe to get service and this will have an impact on increasing client satisfaction as a service user community.